Three Antifungal Proteins From Penicillium expansum: Different Patterns of Production and Antifungal Activity - Garrigues, Sandra; Gandía, Mónica; Castillo, Laia; Coca, María; Marx, Florentine; Marcos, Jose F.; Manzanares, Paloma (Frontiers in Microbiology, 2018)
Antifungal proteins of fungal origin (AFPs) are small, secreted, cationic, cysteine-rich proteins. Filamentous fungi encode a wide repertoire of AFPs belonging to different phylogenetic classes, which offer a great potential to develop new antifungals for the control of pathogenic fungi. The fungus Penicillium expansum is one of the few reported to encode three AFPs each belonging to a different phylogenetic class (A, B and C). In this work, the production of the putative AFPs from P. expansum was evaluated, but only the representative of class A, PeAfpA, was identified in culture supernatants of the native fungus. The biotechnological production of PeAfpB and PeAfpC was achieved in Penicillium chrysogenum with the P. chrysogenum-based expression cassette, which had been proved to work efficiently for the production of other related AFPs in filamentous fungi. Western blot analyses confirmed that P. expansum only produces PeAfpA naturally, whereas PeAfpB and PeAfpC could not be detected. From the three AFPs from P. expansum, PeAfpA showed the highest antifungal activity against all fungi tested, including plant and human pathogens. P. expansum was also sensitive to its self-AFPs PeAfpA and PeAfpB. PeAfpB showed moderate antifungal activity against filamentous fungi, whereas no activity could be attributed to PeAfpC at the conditions tested. Importantly, none of the PeAFPs showed haemolytic activity. Finally, PeAfpA was demonstrated to efficiently protect against fungal infections caused by Botrytis cinerea in tomato leaves and Penicillium digitatum in oranges. The strong antifungal potency of PeAfpA, together with the lack of cytotoxicity, and significant in vivo protection against phytopathogenic fungi that cause postharvest decay and plant diseases, make PeAfpA a promising alternative compound for application in agriculture, but also in medicine or food preservation.